1979
DOI: 10.1901/jeab.1979.31-239
|View full text |Cite
|
Sign up to set email alerts
|

CHANGEOVER RATIO EFFECTS ON CONCURRENT VARIABLE‐INTERVAL PERFORMANCE1

Abstract: Rats' bar-pressing was maintained by concurrent variable-interval schedules of reinforcement. A fixed-ratio of pulls on a chain (the changeover ratio) was required for switching between schedules. The first experiment employed equal variable-interval schedules and symmetrical changeover ratios. Increasing these ratios resulted in a decrease in the rate of switching between schedules and an increase in local response rate. In the second experiment, a range of asymmetrical changeover ratios was used with equal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Similar results were reported by Bourland and Miller (1978) and Killeen (1972). On the other hand, Guilkey, Shull, and Brownstein (1975) and White (1979) failed to observe this rate difference when they used a FR changeover requirement. Pliskoff, Cicerone, and Nelson (1978) …”
Section: ()Jsupporting
confidence: 83%
See 2 more Smart Citations
“…Similar results were reported by Bourland and Miller (1978) and Killeen (1972). On the other hand, Guilkey, Shull, and Brownstein (1975) and White (1979) failed to observe this rate difference when they used a FR changeover requirement. Pliskoff, Cicerone, and Nelson (1978) …”
Section: ()Jsupporting
confidence: 83%
“…Second, it was consistently found that the differences between COD and post-COD response rates were greatly reduced when a COD of variable, rather than fixed, duration was used. Other researchers (Guilkey et al, 1975;Pliskoff et al, 1978;White, 1979) have also failed to obtain a substantial increase in response rates immediately after the CO response when they used a FR changeover requirement instead of a COD of fixed duration. The results of their experiments together with the present findings indicate that elevated response rates immediately after the CO response may occur only when a COD of fixed duration is used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that increasing the ratio required to switch schedules, under concurrent scheduling in one key, will increase the time a pigeon spends in one schedule before it makes a switch response (Findley, 1958). More specifically, White (1979) has shown that switching between concurrent variableinterval schedules in rats becomes less likely when the FR requirement for the switching response is increased. That is, increasing the cost of switching increases persistence in one schedule before a switch response is performed.…”
Section: Methodsmentioning
confidence: 99%
“…Second, no study reported a significant difference between the local rates of reinforcement when the components differed in only minor ways, such as the discriminative stimuli used to signal the components or the position of the operanda that produced reinforcers (Marcucella & Margolius, 1978;McSweeney & DeRicco, 1976;White, 1979, Experiment 1).…”
mentioning
confidence: 99%